Sunan Kalijaga dalam Novel Babad Walisongo, Wali Sanga, dan Kisah Dakwah Wali Songo - Mujiningsih, Erlis Nur; Yetti, Erli (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2015)
This research aims to demonstrate that the novels Wali Sanga by Shashangka, Babad Walisongo by Yudhi AW, and Kisah Dakwah Wali Songo by Kusuma represent the crystallization of discourse interaction surrounding the Walisongo. The scope of this study is to examine how these three novels construct and represent discourse interactions across various narrative perspectives on the Walisongo. This study employs a qualitative research method. The data sources are the novels Babad Walisongo by Yudhi AW, Wali Sanga by Shashangka, and Kisah Dakwah Wali Songo by Kusuma. The data consist of words, sentences, and discourses found in the three novels. The data were analyzed using a hermeneutic approach and the sociology of literature perspective. The results show that Wali Sanga by Shashangka and Babad Walisongo by Yudhi AW successfully present the crystallization of discourse interaction surrounding the Walisongo, whereas Kisah Dakwah Wali Songo by Kusuma does not exhibit the same characteristic.